Expansion Mechanism and Properties of Magnesium Oxide Expansive Hydraulic Cement for Engineering Applications - Siqi Li; Yecheng Feng; Jinbo Yang (Advances in Materials Science and Engineering)
The expansion mechanism of magnesium oxide expansive hydraulic cement as a novel expansive hydraulic cement was reviewed. Anisotropic crystallization results in crystal growth pressure, causing volume expansion while also increasing the porosity of the whole system. The theoretical relationship between porosity and expansion was analyzed. A basic method is given for predicting the expansion rate considering the expansive agent content in MgO expansive hydraulic cement. A concise equation is proposed for calculating the ultimate expansion. A theoretical relationship between porosity and expansion is presented. The compressive strength and durability of magnesium oxide expansive hydraulic cement were analyzed considering porosity changes and compared with hydraulic cement. If the expansion rate exceeds 0.8%, the mechanical properties and durability changes caused by porosity should be considered. If magnesium oxide expansive concrete is used with restraining in real structure, extra compressive stress is generated and the porosity decreases, compared with that during free expansion. In particular, for strain-hardening cementitious composites, expansion confined with the fibers present in the composite is beneficial for refining cracks and improving the self-healing ability of these materials whenever exposed to humid environments. This paper describes the expansion mechanism and properties of magnesium oxide expansive hydraulic cement for engineering applications.